2018
DOI: 10.1182/blood-2018-99-112976
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Type 3 Von Willebrand Disease

Abstract: Background: Von Willebrand disease (vWD) is the most common inherited bleeding disorder worldwide. Genetic mutations in the von Willebrand gene may result in either quantitative (Types 1 and 3 vWD) or qualitative defects (Type 2 vWD) of von Willebrand Factor (vWF). Type 3 is the rarest and most severe form of vWD, resulting in a virtual absence of vWF. Type 3 vWD follows autosomal recessive inheritance and is most often reported in patients who are homozygous for the same gene mutation. We report a patient wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Type III vWD is considered the most severe form of von Willebrand Disease. Studies conducted in different regions of the world have shown different mutations [ 8 , 9 , 10 , 11 ]. Scarce data is available regarding the Pakistani Population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type III vWD is considered the most severe form of von Willebrand Disease. Studies conducted in different regions of the world have shown different mutations [ 8 , 9 , 10 , 11 ]. Scarce data is available regarding the Pakistani Population.…”
Section: Discussionmentioning
confidence: 99%
“…The gene of VWF is located on chromosome 12p having 52 exons encoding a protein of 2813 amino acids [ 7 ]. Worldwide studies have revealed that mutations are spread throughout the entire span of genes and few studies have reported that mutations in certain sites are more prevalent in a particular population [ 8 , 9 , 10 , 11 ]. In addition to the inherited form, several other forms of the disease have been reported, including autoantibodies against VWF and conditions that may cause rapid degradation and clearance of VWF and adsorption of VWF on malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, even compound heterozygous inheritance has been identified. 5 Epidemiological data predominantly from western literature estimates a prevalence of 0.1-5 per million. 6 Trasi et al postulated that type 3 patients are more numerous in India owing to a high rate of consanguineous marriages in certain communities and an underdiagnosis of milder variants.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their lack of VWF, these patients have low factor VIII levels because factor VIII is not being stabilized in plasma by VWF. 19 Type 2: Defective VWF variants In contrast to patients with type 1, type 1C, or type 3 VWD, those with type 2 have normal levels of VWF. However, their VWF has a qualitative defect and does not function as it should.…”
Section: ■ Three Main Types Several Subtypesmentioning
confidence: 99%